2003
DOI: 10.1046/j.1523-1755.2003.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal activation of extracellular signal-regulated kinase in rats with autosomal-dominant polycystic kidney disease

Abstract: We conclude that the MAP kinase pathway is activated to the level of ERK in the abnormal mural epithelial cells lining cysts in animals with a dominantly inherited type of polycystic kidney disease. We suggest that cAMP, acting through PKA, Rap-1 and B-Raf, may contribute to the activation of ERK in a way that complements receptor tyrosine kinase-mediated agonists in the promotion of cyst enlargement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 37 publications
(6 reference statements)
7
90
0
Order By: Relevance
“…Several studies have linked MAPK signaling to cyst formation. Upregulation of ERK has been reported previously in the Han:SPRD rat model for ADPKD and the bcl-2 Ϫ/Ϫ mouse model for cystic kidney disease (27,28). Increased activity of JNK was reported recently in small cysts in another mouse model for polycystic kidney disease (29).…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have linked MAPK signaling to cyst formation. Upregulation of ERK has been reported previously in the Han:SPRD rat model for ADPKD and the bcl-2 Ϫ/Ϫ mouse model for cystic kidney disease (27,28). Increased activity of JNK was reported recently in small cysts in another mouse model for polycystic kidney disease (29).…”
Section: Discussionmentioning
confidence: 74%
“…Nagao et al (19) reported increased expression of P-ERK in the cyst epithelium of Han:SPRD rats, a model of autosomal dominant PKD (ADPKD). Increased ERK activity in cyst epithelium therefore may be a common feature of cystic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The functional significance of these observations is profound. In the kidney, ERK1/2 is expressed in all nephron segments and plays an important role in multiple physiological (33) and pathological processes (30). In contrast to other nephron segments, ERK1/2 appears to have basal activity in distal nephron cells (31,34), consistent with tonic inhibition of Na ϩ transport by the ERK pathway.…”
Section: Gilz1 and Sgk1 Synergistically Stimulate Enac Cell Surface Ementioning
confidence: 97%
“…4). This association of PI3K and Raf-1 pathway components into an ion transport regulatory complex provides a novel mechanism for achieving signaling specificity (9,10,(28)(29)(30)(31). Through this mechanism, ion transport can be selectively stimulated while having little or no effect on context-inappropriate targets.…”
Section: Gilz1 and Sgk1 Synergistically Stimulate Enac Cell Surface Ementioning
confidence: 99%